2015
DOI: 10.1080/00036811.2015.1068297
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Navier–Stokes equations with non-standard conditions for blood flow in atherosclerotic artery

Abstract: In this paper, we consider the blood flow in a stenosed artery. We give an analytical study of the equations for a non-Newtonian fluid modeling the blood for which the behavior is obeying to Carreau's law. The case we treat is different than classic cases where the total pressure is in the natural boundary conditions. For this, we use the Faedo-Galerkin method to prove the existence of a weak solution for the fluid problem. Then we use a coupled approach between the fluid equations and the solid model of the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 16 publications
0
14
2
Order By: Relevance
“…In the case of a moving wall, the highest von Mises stress (13.48 KPa) is observed in the region upstream the stenosis, whereas for the fixed wall configuration the highest value (10.45 KPa) is observed downstream the stenosis. This result is in contradiction with the study presented in [3] where the maximum value of the von Mises stress is located upstream the stenosis in the case of the rigid wall. However, two major considerations distinguish our study: (1) the inlet pressure wave and the absorbing BC chosen for the inlet and outlet, respectively and (2) the differentiation between Young modulus values for the vessel wall (E = 3 · 10 5 Pa in the upstream and downstream extended sections and E = 6 · 10 5 Pa in the vessel wall surrounding the plaque).…”
Section: 2contrasting
confidence: 99%
See 2 more Smart Citations
“…In the case of a moving wall, the highest von Mises stress (13.48 KPa) is observed in the region upstream the stenosis, whereas for the fixed wall configuration the highest value (10.45 KPa) is observed downstream the stenosis. This result is in contradiction with the study presented in [3] where the maximum value of the von Mises stress is located upstream the stenosis in the case of the rigid wall. However, two major considerations distinguish our study: (1) the inlet pressure wave and the absorbing BC chosen for the inlet and outlet, respectively and (2) the differentiation between Young modulus values for the vessel wall (E = 3 · 10 5 Pa in the upstream and downstream extended sections and E = 6 · 10 5 Pa in the vessel wall surrounding the plaque).…”
Section: 2contrasting
confidence: 99%
“…They showed that considering the classical models of interaction between the blood flow (modeled as a Newtonian fluid), the vessel wall and the atherosclerotic plaque, the risk of rupture is less predictive because it underestimates the stress over the plaque comparing with the case where blood is modeled as a non-Newtonian fluid. These previous results were extended by considering a 3D geometry of an idealized blood vessel in order to be more realistic, the aim being to analyze the evolutionary non-linear 3D flow characteristics of blood in a stenosed artery [3]. However, for the numerical simulations based on the theoretical study, the fluid and the structures were described using a 2D axi-symmetric model in order to reduce the overall computational complexity.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…On the one hand, a realistic blood flow simulation requires the use of an adequate flow model. For instance, Boujena et al [5] presented a non-Newtonian flow model adapted to describe blood flow in the presence of atherosclerosis. Simulation in their paper was performed in 2D and 3D simplified geometries.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the choice of suitable boundary conditions is crucial. In our previous paper [1], we presented a first virtual FFR estimation using the generalized fluid model in [5] and conducted different simulations to study the impact of the lesions parameters on the FFR value. However, we considered a simplified 2D geometry and reduced boundary conditions.…”
Section: Introductionmentioning
confidence: 99%